Individualized breastfeeding support for acutely ill, malnourished infants under 6 months old. Issue 1 (2nd August 2019) - Mwangome, Martha; Murunga, Sheila; Kahindi, Jane; Gwiyo, Prinilla; Mwasho, Grace; Talbert, Alison; Kiige, Laura; Samburu, Betty; Mturi, Neema; Abubakar, Amina; Jones, Caroline; Berkley, James A.
Abstract: Reestablishing exclusive breastfeeding is the cornerstone of the 2013 World Health Organization (WHO) treatment guidelines for acute malnutrition in infants less than 6 months. However, no studies have investigated guideline implementation and subsequent outcomes in a public hospital setting in Africa. To facilitate implementation of the WHO 2013 guidelines in Kilifi County Hospital, Kenya, we developed standard operating procedure, recruited, and trained three breastfeeding peer supporters (BFPS). Between September 2016 and January 2018, the BFPS provided individual breastfeeding support to mothers of infants aged 4 weeks to 4 months admitted to Kilifi County Hospital with an illness and acute malnutrition (mid‐upper‐arm circumference < 11.0 cm OR weight‐for‐age z score < −2 OR weight‐for‐length z score < ‐2). Infants were followed daily while in hospital then every 2 weeks for 6 weeks after discharge with data collected on breastfeeding, infant growth, morbidity, and mortality. Of 106 infants with acute malnutrition at admission, 51 met the inclusion criteria for the study. Most enrolled mothers had multiple breastfeeding challenges, which were predominantly technique based. Exclusive breastfeeding was 55% at admission and 81% at discharge; at discharge 67% of infants had attained a weight velocity of >5 g/kg/day for three consecutive days on breastmilk alone. Gains in weight‐for‐length z score and weight‐for‐age z score were generally not sustained beyond 2 weeks after discharge. BFPS operated effectively in an inpatient setting, applying the 2013 updated WHO guidelines and increasing rates of exclusive breastfeeding at discharge. However, lack of continued increase in anthropometric Z scores after discharge suggests the need for more sustained interventions.